Calcium upregulation by percutaneous administration of gene therapy in patients with cardiac disease (CUPID 2): a randomised, multinational, double-blind, placebo-controlled, phase 2b trial. Issue 10024 (19th March 2016) - Greenberg, Barry; Butler, Javed; Felker, G Michael; Ponikowski, Piotr; Voors, Adriaan A; Desai, Akshay S; Barnard, Denise; Bouchard, Alain; Jaski, Brian; Lyon, Alexander R; Pogoda, Janice M; Rudy, Jeffrey J; et al.
Summary: Background: Sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase (SERCA2a) activity is deficient in the failing heart. Correction of this abnormality by gene transfer might improve cardiac function. We aimed to investigate the clinical benefits and safety of gene therapy through infusion of adeno-associated virus 1 (AAV1)/SERCA2a in patients with heart failure and reduced ejection fraction. Methods: We did this randomised, multinational, double-blind, placebo-controlled, phase 2b trial at 67 clinical centres and hospitals in the USA, Europe, and Israel. High-risk ambulatory patients with New York Heart Association class II–IV symptoms of heart failure and a left ventricular ejection fraction of 0·35 or less due to an ischaemic or non-ischaemic cause were randomly assigned (1:1), via an interactive voice and web-response system, to receive a single intracoronary infusion of 1 × 10 13 DNase-resistant particles of AAV1/SERCA2a or placebo. Randomisation was stratified by country and by 6 min walk test distance. All patients, physicians, and outcome assessors were masked to treatment assignment. The primary efficacy endpoint was time to recurrent events, defined as hospital admission because of heart failure or ambulatory treatment for worsening heart failure. Primary efficacy endpoint analyses and safety analyses were done by modified intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01643330 . Findings: Between July 9, 2012, and Feb 5, 2014, we randomly assigned 250 patients to receive either AAV1/SERCA2a (n=123) or placebo (n=127); 243 (97%) patients comprised the modified intention-to-treat population. Patients were followed up for at least 12 months; median follow-up was 17·5 months (range 1·8–29·4 months). AAV1/SERCA2a did not improve time to recurrent events compared with placebo (104 vs 128 events; hazard ratio 0·93, 95% CI 0·53–1·65; p=0·81). No safety signals were noted. 20 (16%) patients died in the placebo group and 25 (21%) patients died in the AAV1/SERCA2a group; 18 and 22 deaths, respectively, were adjudicated as being due to cardiovascular causes. Interpretation: CUPID 2 is the largest gene transfer study done in patients with heart failure so far. Despite promising results from previous studies, AAV1/SERCA2a at the dose tested did not improve the clinical course of patients with heart failure and reduced ejection fraction. Although we did not find evidence of improved outcomes at the dose of AAV1/SERCA2a studied, our findings should stimulate further research into the use of gene therapy to treat patients with heart failure and help inform the design of future gene therapy trials. Funding: Celladon Corporation.